STUDENT SATISFACTION OF SERVICE QUALITY EDUCATION IN JEMBER - Nurul Qomariah (Journal of Business & Banking, 2014)
This study aims to analyze the importance and performance of educational services. Thequality of service consists of tangible, reliability, responsiveness, assurance and empathy.The data were obtained by distributing questionnaires to students of the Faculty of Economics,University of Muhammadiyah Jember with sample 60 respondents selected by purposivesampling. Customer satisfaction index is used to analyze the level of overall student satisfaction.For identifying performance improvement priorities, the Analysis method used consistsof two components: quadrant analysis and gap analysis. The results showed that the overallperformance of students was satisfied with education services to the student satisfaction indexscore was 86.60 percent. Quadrant analysis shows that the dimensions of assurance, reliability,responsiveness, and empathy are considered an important dimension and good performancein accordance with the expectations of the students so that this dimension needs tobe maintained and enhanced performance. The dimension that is considered less good is thatof tangibles.